Linking Talent and Knowledge Management with Employee Retention to Employee Performance (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Human resources are a vital asset for companies, significantly influencing their success and growth. This study investigates how talent management, knowledge management, and employee retention affect employee performance at PDAM Tirta Moedal Kota Semarang, using a quantitative approach with a sample of 108 employees selected through purposive sampling. Data was collected via questionnaires and analyzed with SPSS Statistics version 30.0. The findings show that talent management positively impacts employee performance, while knowledge management and employee retention do not significantly affect it. However, all three factors combined show a simultaneous influence on performance. The study highlights the importance of effective talent management and recommends further research to adopt a 5% standard error for more accurate results.
Keywords: Talent Management; Knowledge Management; Employee Retention; Employee Performance